Investigating the optical, photosensitivity and photocatalytic properties of double perovskites A2LuTaO6 (A = Ba, Sr): A combined experimental and density functional theory study. Issue 12 (15th August 2019) - Halder, Saswata; Sheikh, Md. Sariful; Maity, Ritwik; Ghosh, Binita; Sinha, T.P.
Abstract: The photophysical properties of double perovskite oxides A2 LuTaO6 (ALT; A = Ba, Sr) are investigated to design new photovoltaic materials by exploring the photosensing and photocatalytic properties. The Raman spectra for Ba2 LuTaO6 (BLT) and Sr2 LuTaO6 (SLT) agree well with the room temperature crystal structures of the materials. The electronic band structure of BLT and SLT show a direct band gap at the Γ-point with the optical excitations occurring between the O p states and the Ta d states. The calculations reveal a comparable visible light absorption coefficient to other well-known ferroelectric perovskite solar cell candidates. In addition, an anisotropy is also developed in the optical properties as the symmetry gets reduced due to the prevalent octahedral distortions. The electrical charge transport, measured under both dark and illuminated conditions, is analyzed in terms of the thermionic emission theory of metal-semiconductor junction. The observed decrease in the Schottky diode resistance (Rs ) for all the materials can be correlated to the decrease in the potential barrier upon light illumination. The observed trends in photosensitivity are correlated to the changing symmetry and bond angles. The degradation of organic pollutant rhodamine-B (Rh-B) using BLT and SLT as photocatalysts are shown to possess relatively high degradation rates. The photodegradation kinetics is analysed in terms of the band gap, particle size, dielectric properties and structural changes. This work serves as a model to design new optoelectronic materials by correlating the theoretical electronic and optical properties to the experimentally observed optoelectronic and photocatalytic properties.